ANALISIS PENDAPATAN PEDAGANG PASAR BARU KENCONG KABUPATEN JEMBER - Christi Mei Wulandari (Program Studi Ekonomi Pembangunan, 2017)
AbstractThe market was the one place that pervaded a lot of labors, on the other hand for middle society to lower society that had less education could maked the market as a place of business to trades. Therefore will be decreased unemployment rate and increased income for society and give prosperity for all society. The aim of this research is to find out an influence of financial capital and time work togetherness to Baru Kencong market trader’s income Jember. This research was quantitative descriptive research. Population within this research that was market traders, sample was used as much as 48 traders. Technical data analysis was using multiple linear regression. The result of this research was financial capital that had significant effect to new Kencong market trader’s income Jember regency. By showing it that tcount is bigger than ttable (19.49034>2.014103). time work will be significant affected to new Kencong market trader’s income Jember regency. By showing it that tcount is bigger than ttable (6.679001>2.014103). financial capital and time work simultaneously will be significant effected to new Kencong market trader’s income Jember regency. Magnitude effect can be showed with determinant coefficient values (